profile
Опубликовано 1 год назад по предмету Алгебра от pro100tabletk

Help me!
 frac{a}{ sqrt{ab} +b} + frac{b}{ sqrt{ab}-a } -  frac{a+b}{ sqrt{ab} }

  1. Ответ
    Ответ дан Матов
    frac{a}{sqrt{ab}+b}+frac{b}{sqrt{ab}-a}-frac{a+b}{sqrt{ab}}=\
frac{a(sqrt{ab}-a)+b(sqrt{ab}+b)}{(sqrt{ab}+b)(sqrt{ab}-a)} -frac{a+b}{sqrt{ab}}=\
frac{asqrt{ab}-a^2+bsqrt{ab}+b^2}{(sqrt{ab}+b)(sqrt{ab}-a)} - frac{a+b}{sqrt{ab}}=\
frac{(asqrt{ab}-a^2+bsqrt{ab}+b^2)sqrt{ab}-(a+b)(sqrt{ab}+b)(sqrt{ab}-a)}{sqrt{ab}(sqrt{ab}+b)(sqrt{ab}-a)}=\
frac{a^2b-a^2sqrt{ab}+b^2a+b^2sqrt{ab}-b^2sqrt{ab}+a^2sqrt{ab}}{ab^2-a^2b}=\
frac{a^2b^2+ab^2}{ab^2-a^2b}=
    frac{ab(a+b)}{ab(a-b}}=frac{a+b}{a-b}

    1. Ответ
      Ответ дан Матов
      на пользу